Mucosal tenascin C content in inflammatory and neoplastic diseases of the large bowel - Riedl, Stefan; Kadmon, Martina; Tandara, Andrea; Hinz, Ulf; Möller, Peter; Herfarth, Christian; Faissner, Andreas (Diseases of the colon & rectum, 1998)
PURPOSE: Tenascin C is a glycoprotein of the extracellular matrix. It is upregulated during embryologic development, wound healing, and under conditions of normal and neoplastic growth. Most available data on tenascin C expression in tissues is based on immunohistologic studies. The present study was designed to quantify tissue concentrations in patients with inflammatory and neoplastic diseases of the large bowel. METHODS: Fifty patients with ulcerative colitis, 19 patients suffering from familiar adenomatous polyposis without malignant transformation, and 69 patients with colorectal carcinoma were investigated. Tenascin C concentrations in tissue extracts were determined by semiquantitative Western blotting. RESULTS: The tenascin C tissue concentration of normal mucosa was 2.6±3.4 µg/mg (n=55), 2.9±2.1 µg/mg in colorectal adenomas (n=19), 7.5±4.7 µg/mg in ulcerative colitis (n=50), and 18±15 µg/mg in colorectal carcinomas (n=69; mean ± standard deviation). In ulcerative colitis, the mucosal tenascin C content correlated with histopathologic disease activity. No differences were found between subgroups of adenomas or carcinomas. CONCLUSIONS: Tenascin C tissue concentrations were not altered in adenomas, slightly elevated in ulcerative colitis, and substantially increased in colorectal carcinomas. Although less useful as a diagnostic parameter, tenascin C tissue levels serve as an instrument for assessing the activity of stromal remodeling in largebowel diseases generally. Specifically, they may reflect disease activity in ulcerative colitis.
Gesehen am 23.10.2025